The Neotropical species of Atractodes (Hymenoptera, Ichneumonidae, Cryptinae), I: the A. propodeator and A. altoandinus species-groups - Bordera, Santiago; Mazón, Marina; Sääksjärvi, Ilari E. (Zootaxa, 2016)
The Neotropical species of the cryptine genus Atractodes are studied, and four species-groups are proposed. In this paper, A. altoandinus and A. propodeator species-groups are diagnosed. The former species-group occurs from southern Mexico to Brazil and includes some of the largest Atractodes species ever found, all possessing a strongly sloped propodeum; the latter species-group is only known from the Chilean Andes and includes one of the smallest species of Atractodes, characterised by a very short and curved tergite I and short first flagellomere. Four species, A. altoandinus, A. propodeator, A. reijoi and A. verapacensis are described as new. An illustrated identification key to all species-groups and to species of the A. propodeator species-group is provided.